2001
DOI: 10.4049/jimmunol.167.10.5880
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Administration of Anti-PcrV F(ab′)2 in Sepsis Associated with Pseudomonas aeruginosa

Abstract: The effects of rabbit-derived polyclonal Ab against PcrV, a protein involved in the translocation of type III secreted toxins of Pseudomonas aeruginosa, was investigated in two animal models of P. aeruginosa sepsis. In a mouse survival study, the i.v. administration of anti-PcrV IgG after the airspace instillation of a lethal dose of P. aeruginosa resulted in the complete survival of the animals. In a rabbit model of septic shock associated with Pseudomonas-induced lung injury, animals treated with anti-PcrV I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 35 publications
2
105
0
Order By: Relevance
“…Most strains of P. aeruginosa secrete virulence factors by the type III secretion system [6,7]. The role of proteins secreted and translocated across eukaryotic cell plasma membranes by the type III secretion system has been highlighted both in vitro [8,9] and in animal models in recent years [10]. Neutralization of the type III secretion proteins have shown to prevent septic shock and an improved survival in a mouse model of P. aeruginosa infection [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most strains of P. aeruginosa secrete virulence factors by the type III secretion system [6,7]. The role of proteins secreted and translocated across eukaryotic cell plasma membranes by the type III secretion system has been highlighted both in vitro [8,9] and in animal models in recent years [10]. Neutralization of the type III secretion proteins have shown to prevent septic shock and an improved survival in a mouse model of P. aeruginosa infection [10].…”
Section: Introductionmentioning
confidence: 99%
“…The role of proteins secreted and translocated across eukaryotic cell plasma membranes by the type III secretion system has been highlighted both in vitro [8,9] and in animal models in recent years [10]. Neutralization of the type III secretion proteins have shown to prevent septic shock and an improved survival in a mouse model of P. aeruginosa infection [10]. In addition, type III secretion has been associated with more severe clinical disease in human studies [11].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of PcrV in clinical isolates of P. aeruginosa is associated with morbidity and mortality in infected patients [12]. Previous studies have shown that anti-PcrV IgG protects animals from acute P. aeruginosa infection [7,8]. In these studies, anti-PcrV was given to animals at the same time, or soon after, inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…The polyclonal rabbit-derived anti-PcrV Ab and pre-immune serum-derived control Ab used in the present study were prepared and stored at -80uC, as previously reported [8]. The mice were separated into three groups; each group received i.p.…”
Section: Antibody Administrationmentioning
confidence: 99%
See 1 more Smart Citation